BEDSIDE TEACHING-MAKING IT AN EFFECTIVE INSTRUCTIONAL TOOL - Khan, Ishtiaq Ali (Journal of Ayub Medical College Abbottabad, 2014)
College of Medicine, Northern Border University Arar, Kingdom of Saudi Arabia Background: Bedside teaching is defined as any teaching in the presence of patient and is the core teaching strategy during the clinical years of a medical student. Although it is considered the most effective method to teach clinical and communication skills but its quality is deteriorating with the passage of time. The objective of this study is to explore faculty's perceptions about bedside teaching. Methods: This study was conducted in clinical disciplines of Ayub Medical College and hospital Abbottabad, Pakistan from January 2012 to July 2012. Pragmatic paradigm was selected to gather both quantitative and qualitative information. Data was collected sequentially to validate findings. Perceptions of all professors of clinical subjects about bed side teaching were recorded on a close-ended structured questionnaire. Then in-depth interviews were taken from 5 professors using an open ended questionnaire. Quantitative data was analysed using SPSS-16. Qualitative research data was analysed through content analysis. Results: Out of 20 professors of clinical departments 18 agreed to respond to the questionnaire assessing their perceptions about bed side teaching. Non-existence of bedside teaching curriculum, lack of discipline in students and faculty, lack of accountability, poor job satisfaction and low salary were identified as major factors responsible for decline in quality of bedside teaching. Most of them advocated that curriculum development, planning bedside teaching, implementation of discipline and accountability, improved job satisfaction and performance based promotions will improve quality of clinical teaching. Conclusions: Curriculum development for bedside teaching, institutional discipline, application of best planning strategies, performance based appraisal of faculty and good job satisfaction can make bedside teaching an effective instructional tool. Keywords: Bedside teaching, instructional tool, clinical curriculum, clinical teaching planning